Peran Dan Tanggung Jawab Notaris Terkait Dengan Prinsip Kehati-Hatian Dalam Menghindari Pemalsuan Akta Yang Dilakukan Oleh Staf Notaris - Zuhardi, Sylvia Ulfa; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In the implementation of duty, a Notary is constituted by law to be given special authorization in accordance with authentic deeds. The authentic deeds made by Notary is acknowledged to have strength of evidence and proven to be infallible as evidence before the court. Related to such authorization, a Notary ought to be aware of precautionary principle to avoid any violation or mistake that can lead to legal issues. In relation with the mentioned matters, before making deeds, Notary is ought to conduct research and examine any facts related with the deeds refer to prevailing laws. The purpose of the precautionary principle which is bear by Notary to omit, or at least decrease the risk of misused of identities of the parties involved and to prevent forgery.